FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEIKUTSERTAAN PASANGAN USIA SUBUR DALAM PROGRAM KELUARGA BERENCANA DI DESA OBEN KECAMATAN NEKAMESE - nur, asyah (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2024)
Based on the recapitulation compiled from the regions, the achievements of family planning services at the same time as commemorating National Family Day (Harganas) in 2023 were attended by 1,273,566 of the target of 1,244,348 acceptors. The three provinces with the highest achievements were South Kalimantan (201.3%), Lampung (181%), and DI Yogyakarta (172.6%). The three provinces with the lowest achievements include Papua (27.1%), North Kalimantan (54.40%), and East Nusa Tenggara (59.9%). The problem of achieving the family planning program in NTT is still in the lowest category compared to other provinces in Indonesia. Oben village is one of the villages in the Kupang district with a number of couples of childbearing age (PUS) who do not participate in the family planning program, namely 86 PUS. The aim of this research is to determine the factors related to the participation of couples of childbearing age in participating in the Family Planning Program in Oben village. The type of research used in this research is quantitative with a cross sectional method. The population is all PUS in Oben village, namely all PUS aged 15-49 years and still menstruating. The total sample in this study was 86 samples. This research was carried out by interviews using a questionnaire to find out the data you wanted to research. Then the researchers carried out univariate and bivariate analyzes and tested using chi-square. Based on the research results, it was found that there was a significant relationship between age, education and parity and a couple's participation in the family planning program in Oben village. Keywords: Parity, Education, Age, Family planning